Effect of Group Cognitive Behavioral Therapy on Inefficient Beliefs and Marital Satisfaction in Pregnant Women With the Fear of First Childbirth - Barat Ali Ghavami; Bahram Ali Ghanbari Hashem Abad; Mohammad Reza Saffarian; Masoud Khakpour (Gonabad University of Medical Sciences, 2020)
Background: The present study examined the effect of Group Cognitive Behavioral Therapy (GCBT) on inefficient beliefs and marital satisfaction in pregnant women with the Fear of First Childbirth (FoFC).  Methods: This was a quasi-experimental study with a Pre-test-Post-test and a control group design. The study participants were pregnant women with FoFC who visited Quchan health center in 2018. The study participants were selected using a questionnaire of childbirth fear (as screening) of women with the fear of giving birth. Then, by providing an informed consent form, women volunteering to participate in the project (39 people) were randomly assigned to the experimental (20 people) and control (19 people) groups. The experimental group attended ten 90-minute GCBT sessions. Three questionnaires (Attitude to Childbirth, Jones' Irrational Beliefs, Afrooz Marital Satisfaction) were used to obtain the required data.  Results: The study findings revealed that GCBT significantly affected inefficient beliefs and marital satisfaction in studied pregnant women with FoFC (P<0.001). Moreover, There was a significant difference between Pre-test and Post-test mean scores in terms of inefficient beliefs and marital satisfaction (P<0.001). Conclusion: GCBT was effective in inefficient beliefs and marital satisfaction; thus, this method is recommended to improve the relationship between pregnant women and their spouses during pregnancy.